2017
DOI: 10.1002/cam4.1110
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐375/SLC7A11 axis regulates oral squamous cell carcinoma proliferation and invasion

Abstract: We aimed to detect the functions of miR‐375/SLC7A11 axis on oral squamous cell carcinoma (OSCC) cell proliferation and invasion. Expression levels of miR‐375 and SLC7A11 in OSCC tissues and cells were measured with RT‐qPCR and western blot. Targeting site was predicted by TargetScan and confirmed by dual luciferase reporting assay. By way of manipulating the expression level of miR‐375 and SLC7A11 in CAL‐27 and Tca8113 cell lines, the cell biological abilities were evaluated. MTT, colony formation, Transwell, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 39 publications
4
56
0
Order By: Relevance
“…Transport system Xc, combination of SLC7A11 and SLC3A2, plays an important role in cell growth and drug resistance of PANC 13,26 . In this study, we found that overexpression of SLC7A11 could significantly promote PANC cell proliferation and migration, which is consistent with the previous studies in other cancers 5 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Transport system Xc, combination of SLC7A11 and SLC3A2, plays an important role in cell growth and drug resistance of PANC 13,26 . In this study, we found that overexpression of SLC7A11 could significantly promote PANC cell proliferation and migration, which is consistent with the previous studies in other cancers 5 .…”
Section: Discussionsupporting
confidence: 93%
“…MicroRNA (miRNA) is a type of small RNA with about 22 nucleotides in length and widely distributed in eukaryotic cells, characterized with highly conservativity in evolution progress and regulatory functions in cell differentiation, proliferation and apoptosis 3,4 . Studies have shown that miRNA expression is abnormal in tissues of various human tumors, which is significantly different in normal tissues, with distinct tissue specificity that could be used to determine the origin of tumors 5 . Therefore, miRNA plays an important role in differentiation and migration of tumor.…”
Section: Introductionmentioning
confidence: 99%
“…1), which may be related to cell tolerance and the toxicity of impurities. Wu et al reported that miR-375 significantly inhibited OSCC cell viability, proliferation, invasion and migration and induced apoptosis [24]. …”
Section: Discussionmentioning
confidence: 99%
“…[ 8 9 10 11 12 13 ] MicroRNA-375 (miR-375) has been identified to play a tumor-suppressive role in various types of human cancers including hepatocellular carcinoma, non-small cell lung cancer, esophageal cancer, oral squamous cell carcinoma, gastric cancer, pancreatic cancer, colorectal cancer, and prostate cancer. [ 14 15 16 17 ] However, the biological roles of miR-375 in ccRCC have by far not been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%